2019
DOI: 10.1177/1049909119829411
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hygiene Care in Patients With Advanced Disease: An Essential Measure to Improve Oral Cavity Conditions and Symptom Management

Abstract: Background: Oral problems are frequent in palliative care and can cause disabling symptoms such as orofacial pain, dysgeusia, and xerostomia. Even if oral care is an essential aspect of nursing, it is often not considered as a priority, especially when various complex patients’ needs have to be managed. Objective: The aim of this study was to describe oral conditions and evaluate the impact of standard oral care on symptom control and patient’s perceived comfort in a sample of terminally ill patients. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…Despite the multitude of di culties, administering oral care to terminally ill patients is necessary. In a previous study, oral care was shown to increase oral moisture levels, provide relief from oral symptoms, provide a sensation of oral comfort, reduce the degree of dysgeusia, reduce the chances of odontogenic infections, increase the amount of food intake, and improve quality of life [4,5,8,[24][25][26]. Some conclusions were also provided by this present study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Despite the multitude of di culties, administering oral care to terminally ill patients is necessary. In a previous study, oral care was shown to increase oral moisture levels, provide relief from oral symptoms, provide a sensation of oral comfort, reduce the degree of dysgeusia, reduce the chances of odontogenic infections, increase the amount of food intake, and improve quality of life [4,5,8,[24][25][26]. Some conclusions were also provided by this present study.…”
Section: Discussionsupporting
confidence: 65%
“…Because of the general weakness and pain experienced by patients, side effects of cancer treatment or surgery, or depression, most patients ignore their oral health. Consequently, most patients have been reported to show poor oral health at admission into hospice wards [2,3,5,6,10,[23][24][25]. Among our patients, only 2 patients accepted a routine dental follow-up during the past 1-2 years.…”
Section: Discussionmentioning
confidence: 97%
“…Ensuring that patients maintain adequate oral hygiene care may also be helpful for dysgeusia management. 55 Diarrhea and/or constipation have frequently occurred in approximately one-third of patients treated with PARPi maintenance, and are generally grade 1-2 ( Table 3). Other frequent gastrointestinal disorders include abdominal pain and decrease in appetite; however, rates of abdominal pain seem to be similar in the placebo arm, and may also be related to underlying disease (Table 3).…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%
“…The median total OHAT score was 8 on Day 1, and it signi cantly decreased to 3. In conscious patients, during the care process, we used the assessment of care comfort for conscious patients, per a previous study [25]. Of the 17 conscious patients, 15 felt comfortable or slightly comfortable.…”
Section: Strengths and Limitationsmentioning
confidence: 99%